REKAYASA PERANGKAT LUNAK PENCARIAN RUMAH KOST DENGAN DIJKSTRA'S ALGORITHM OPTIMIZATION - Edy Nasri; M Bani Husni (Jurnal Ilmiah Sains dan Teknologi, 2019)
Information needs are very important to help facilitate human life, one of which is the need to obtain information on temporary residence or boarding houses for students, employees and employees whose home is far away. Therefore the author designed a software engineering to make it easier for students, employees and employees to get the location and complete information about boarding houses that will be chosen to be occupied or as a reference for choosing a comfortable boarding house. Applications that are designed can show boarding locations, prices, boarding facilities, boarding rules, boarding house contacts and the fastest route, closest to the boarding house application boarding house where the authors design using Dijkstra's Algorithm Optimization and Google API to help get the shortest route to the place the boarding house intended. The website application that is designed is expected to help facilitate students, employees or entrants to get fast and complete information in searching for boarding house places.